(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
Public procurement is an important element of managing the financial resources of the state. Proper and effective procurement management allows not only to save budget funds, but also to ensure a high-quality level of services provided in the social sphere. Social organizations have their own peculiarities in the management of public procurement. In this article, we will look at the problems and opportunities of organizations working in the fields of healthcare, education and culture, as well as give recommendations on improving the efficiency of the public procurement management process in these organizations.